Pengaruh Storytelling-Based Learning terhadap Hasil Belajar Siswa pada Pembelajaran PAI di Sekolah Dasar - Sitto Rahmana (STAI AL-AMIN, 2025)
This study aims to analyze and describe the improvement of learning outcomes by applying the storytelling-based learning approach to Islamic Religious Education learning in elementary schools. This study is a quantitative study with a quasi-experimental method. The research design applies One Sample Pretest-Posttest Design. The research sample was 30 fifth grade students of SDN 09 2X11 Enam Lingkung, Padang Pariaman Regency. The research instrument was a test of 30 multiple-choice questions. Data analysis used descriptive analysis, normality test, homogeneity test, average difference test and gain normalization test. The results of the study obtained pretest learning outcomes of 65.63 (less) and posttest learning outcomes of 85.3 (Good). Hypothesis testing found that t count 56.7> t table 0.683 with a sig.0.000 <0.05. The results of the analysis showed that Ho was accepted and Ha was rejected, thus there was an average difference between student learning outcomes at the pretest and posttest stages. The N-gain results show that there is an increase in student learning outcomes (pretest-posttest) of 19.67 points with a Gain normalization value of 0.76. This shows that the increase in student learning outcomes by implementing a storytelling-based learning approach to Islamic Religious Education learning is in the moderate category with a percentage of 76%.